2012
DOI: 10.1177/1065912912449697
|View full text |Cite|
|
Sign up to set email alerts
|

Emotions, Campaigns, and Political Participation

Abstract: There has been a scarcity of work examining the political consequences of discrete emotions. This article examines the political effects of several emotions—anger, sadness, fear, and enthusiasm. Emotional ads should influence whether voters become politically active. To test this, two experiments were administered. The first examines emotional responses to campaign messages; the second tests whether emotions influence political participation. The results indicate anger is mobilizing, by increasing participator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 45 publications
3
94
1
10
Order By: Relevance
“…Brader and Marcus () suggested recently that three distinct emotions really matter in U.S. politics: Anger, anxiety, and enthusiasm (see also Marcus, ; Valentino, Brader, Groenendyk, Gregorowicz, & Hutchings, ). For example, Weber () manipulated which personal emotion (e.g., anger, sadness) was evoked with respect to crime in the United States. Although this emotion manipulation was purposefully confounded to maximize systematic variance (that is, not completely standardized across conditions), Weber () found that personal anger (in this specific condition about drugs‐related crime) stimulated political action such as campaign volunteering.…”
Section: Four Converging Themes and A Taxonomy Of Core Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brader and Marcus () suggested recently that three distinct emotions really matter in U.S. politics: Anger, anxiety, and enthusiasm (see also Marcus, ; Valentino, Brader, Groenendyk, Gregorowicz, & Hutchings, ). For example, Weber () manipulated which personal emotion (e.g., anger, sadness) was evoked with respect to crime in the United States. Although this emotion manipulation was purposefully confounded to maximize systematic variance (that is, not completely standardized across conditions), Weber () found that personal anger (in this specific condition about drugs‐related crime) stimulated political action such as campaign volunteering.…”
Section: Four Converging Themes and A Taxonomy Of Core Motivationsmentioning
confidence: 99%
“…For example, Weber () manipulated which personal emotion (e.g., anger, sadness) was evoked with respect to crime in the United States. Although this emotion manipulation was purposefully confounded to maximize systematic variance (that is, not completely standardized across conditions), Weber () found that personal anger (in this specific condition about drugs‐related crime) stimulated political action such as campaign volunteering. Similarly, Valentino et al () found that personal anger mobilized individuals to vote across experimental, survey, and ANES (American National Election Studies) data, and Groenendyk and Banks (2013) found that personal anger predicted political action in an experiment and two different parts of the ANES database.…”
Section: Four Converging Themes and A Taxonomy Of Core Motivationsmentioning
confidence: 99%
“…Our findings may also have practical implications. For one, our findings suggest that those seeking to increase turnout in national elections should make use of party identification and efficacy in their electoral campaigns and political discourse and communication (e.g., Klandermans, ; Weber, ). It is less clear whether political communicators and campaigners should also make use of anger to this end, but at the very least they should be considering what the “right” target of anger would be in the given context.…”
Section: Discussionmentioning
confidence: 93%
“…Outgroup‐directed anger (e.g., anger targeting the government, authorities, or advantaged group in society) plays a prominent role in explaining why people protest, but little is known about the potential of such anger to motivate voting in national elections (cf. Garry, ; Gerber & Rogers, ; Valentino, Brader, Groenendyk, Gregorowicz, & Hutchings, ; Weber, ). It is important to know more about this unknown motivational potential of anger because this potentially provides new insights into the psychology of voting turnout.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the 2008 U.S. presidential election, anger was found to mobilize political participation (Valentino, Brader, Groenendyk, Gregorowicz, & Hutchings, 2011). Examining the political effects of several emotions, Weber (2013) documented that anger enhances participatory intentions. These studies on the effect of emotion on behavior lend plausibility to the idea that emotion may motivate activities on social media.…”
Section: Emotion and Social Media Use For Social Movementsmentioning
confidence: 97%